THE EXPERIENCE OF SOCIAL PEDAGOGUES AND SOCIAL WORKERS WHEN PROMOTING POSITIVE BEHAVIOUR IN CHILDREN AT DAY-CARE CENTRES - Raudeliunaite, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents the study, the purpose of which is to reveal the experience of social pedagogues and social workers when promoting positive behaviour in children at day-care centres. The qualitative type of research was chosen when applying the method of semi-structured inteview. The data of the study were processed by applying the method of data content analysis. 3 social pedagogues and 5 social workers, who work at children day- care centres, participated in the study. The data of the study revealed that when promoting positive behaviour in children at day-care centres social pedagogues and social workers create positive relationships with children and strengthen positive interrelationships between children, have individual conversations with children. Meaningful use of children’s leisure time plays an important role when promoting positive behaviour in children. In this case, it is important that the activities, which are organised for children, would be personally and socially meaningful, that they would encourage independence and responsibility in children and humane relationships. When promoting positive behaviour in children social pedagogues and social workers encourage the culture of teamwork and cooperation in order to maintain partnership relationships with parents of the child and other specialists by sharing their experience and rendering assistance to other.